2016
DOI: 10.1186/s13287-016-0436-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells/multipotent stromal cells (MSCs) are glycolytic and thus glucose is a limiting factor of in vitro models of MSC starvation

Abstract: BackgroundMesenchymal stem/multipotent stromal cells (MSCs) contribute to tissue repair but are challenged during wound healing when the blood supply is disrupted, thereby limiting nutrient delivery. Survival mechanisms against ‘starvation’ include autophagy, which we previously found to enhance differentiation efficiency. MSC response to models of in vitro nutrient deprivation are of great interest for improving MSC survival and therapeutic efficacy; however, the rate-limiting nutrients are unknown.MethodsMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 21 publications
4
45
1
Order By: Relevance
“…These data together confirmed that hBM‐MSC have high resistance to genetic damage as previously demonstrated . Although it has been shown that MSC have high metabolic flexibility , when cultured in vitro they have a glycolytic phenotype being highly dependent on glycolysis and glucose metabolism for energy. Successful culture of MSC in a SF medium with “reduced” nutritional properties, with respect to a “rich” FBS‐containing medium, supports the concept of glucose as a source of energy for cell expansion.…”
Section: Discussionsupporting
confidence: 87%
“…These data together confirmed that hBM‐MSC have high resistance to genetic damage as previously demonstrated . Although it has been shown that MSC have high metabolic flexibility , when cultured in vitro they have a glycolytic phenotype being highly dependent on glycolysis and glucose metabolism for energy. Successful culture of MSC in a SF medium with “reduced” nutritional properties, with respect to a “rich” FBS‐containing medium, supports the concept of glucose as a source of energy for cell expansion.…”
Section: Discussionsupporting
confidence: 87%
“…First, the effect of other degenerate IVD environmental stimuli including other inflammatory cytokines, oxygen tension, pH, limited nutrient supply and osmolarity, which have been shown to impact MSC effector function and viability, were not investigated . For example, studies have shown that MSC metabolism is highly dependent upon the presence of glucose, and that MSCs may be tolerant of or adapt to nutrient deprivation . Moreover, hypoxia may enhance MSC differentiation toward a IVD cell‐like phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms justify the growth inhibitory effects of metformin. On the other hand, among limiting nutritional factors to MSCs, glucose and related metabolisms are the most important factors in survival and normal function of MSCs, especially in comparison to other common nutrients such as serum, oxygen, and amino acid concentrations in culture or in implant sites . Hyperglycemic condition causes undesirable effects on proliferation and differentiation of MSCs .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among limiting nutritional factors to MSCs, glucose and related metabolisms are the most important factors in survival and normal function of MSCs, especially in comparison to other common nutrients such as serum, oxygen, and amino acid concentrations in culture or in implant sites. 27 Hyperglycemic condition causes undesirable effects on proliferation and differentiation of MSCs. 28 Fu and his colleagues suggested that high glucose decreases proliferation of neural stem cells by increased apoptosis and change expression of genes that are associated to cell cycle progression.…”
Section: Celecoxib Induced Secretion Of Gdf-15 From Mscs In Each Glmentioning
confidence: 99%